2006
DOI: 10.1111/j.1538-7836.2006.02058.x
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism and the risk of subsequent symptomatic atherosclerosis

Abstract: Summary. Background: Recently, we reported an association between asymptomatic carotid atherosclerosis and venous thromboembolism (VTE) of unknown origin. We hypothesized that patients with VTE of unknown origin would be at a higher risk of developing symptomatic atherosclerosis than patients with VTE induced by known risk factors. Methods: To examine this hypothesis, we studied 1919 consecutive patients followed prospectively after their first VTE episode. The primary outcome was non-fatal and fatal symptomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
119
1
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(131 citation statements)
references
References 22 publications
2
119
1
7
Order By: Relevance
“…However, a number of studies have shown that idiopathic VTE is associated with an increased risk of subsequent cardiovascular events and that patients with idiopathic VTE have an increased prevalence of asymptomatic atherosclerotic lesions. [38][39][40] Because PCOS is associated with atherosclerotic disease, a relationship with venous diseases needs to be considered. Our findings, therefore, do have connotations that might be relevant in clinical settings.…”
Section: Commentmentioning
confidence: 99%
“…However, a number of studies have shown that idiopathic VTE is associated with an increased risk of subsequent cardiovascular events and that patients with idiopathic VTE have an increased prevalence of asymptomatic atherosclerotic lesions. [38][39][40] Because PCOS is associated with atherosclerotic disease, a relationship with venous diseases needs to be considered. Our findings, therefore, do have connotations that might be relevant in clinical settings.…”
Section: Commentmentioning
confidence: 99%
“…Our data and those from the literature may strengthen the hypothesis of an association between atherosclerosis and venous thrombosis, which is the subject of animated discussion. [3][4][5][6][7]13,14,32,33 Analyzing the components of the metabolic syndrome individually, abdominal obesity was demonstrated to be of predictive value for both coronary heart disease and VTE. 9,34 Dyslipidemia has long been known to be a risk factor for atherothrombotic disorders.…”
mentioning
confidence: 99%
“…There is accumulating evidence for an association between VTE and atherosclerosis. [3][4][5][6][7] VTE and atherosclerosis may share common risk factors. For example, obesity in general and abdominal obesity in particular are also well accepted risk factors for VTE and were reported to be associated with impaired fibrinolytic activity, which may be a predisposing mechanism to arterial as well as to venous thrombosis.…”
mentioning
confidence: 99%
“…For instance, the 10-year cumulative risk of symptomatic vascular events among patients with idiopathic DVT is 25.4%, compared with 12.9% in those with secondary VTE [26]. Patients with idiopathic DVT also have a higher prevalence of atherosclerotic risk factors (diabetes, hypertension, and hypercholesterolemia) and coronary artery calcium than control group without VTE [27].…”
Section: ) Symptomsmentioning
confidence: 99%